The Connection between Student Learning Independence, Responsibility and Discipline in An-Nizam Private High School in Medan - Prawidhy Khairunnisa; Surya Hardjo; M. Abrar Parinduri (LP2M STIT Palapa Nusantara, 2023)
The purpose of this study was to determine the relationship between discipline and responsibility with student learning independence at An-Nizam Private High School Medan. This research is a quantitative study with a population of 140 students at An-Nizam Private High School Medan. Data collection techniques use three scales, including the scale of discipline, scale of responsibility, scale of learning independence. The results of the study show the first hypothesis that there is a positive correlation between discipline and student learning independence. The second hypothesis is known that there is a positive relationship between responsibility and learning independence seen and the third hypothesis there is a significant relationship between discipline and responsibility and learning independence. It is known from the coefficient Freg = 166.326 with p <0.05, and the correlation coefficient r = 0.880 with p <0.05 and R^2 = 0.774, it is concluded that discipline and responsibility simultaneously affect student learning independence, the contribution of both in raises student learning independence is equal to 77.4%. Based on the research results the hypothesis is accepted.